Volunteering and mentoring as prosocial strategies for professional training of a future physical education teacher - Eroshenkova E.I.; Isaev I.F.; Mikhaylova D.I.; Tarasova S.I.; Gorbatenko Yu.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identifying the experience and prospects for including prosocial strategies of volunteering and mentoring in the professional training of future physical education teachers. Methods and structure of the study. The online survey method «Prosocial strategies in teacher training» was used (E.I. Eroshenkova, D.I. Mikhaylova). The sample consisted of 67 students of 1-4 years of study at the Faculty of Physical Education of Belgorod State National Research University. Results and conclusions. Multidirectional university experience in volunteering and mentoring at the faculty was identified. A number of prospects and recommendations for the implementation of prosocial strategies in the professional training of future physical education teachers have been identified: 1) inclusion of students in volunteer practice; 2) providing students with a variety of volunteering experiences; 3) support for traditional and alternative mentoring at the university; 4) expanding the boundaries of pedagogical mentoring and correlating it with the needs of the individual, family, state and society.